A peculiar bonebed reinforces gregarious behaviour for the Triassic dicynodont Dinodontosaurus. (2nd July 2020) - Ugalde, Gianfrancis D.; Müller, Rodrigo T.; de Araújo-Júnior, Hermínio Ismael; Dias-da-Silva, Sérgio; Pinheiro, Felipe L.
ABSTRACT: The discovery and study of bonebeds can provide unique information on the biology of extinct animals. Here we interpret the taphonomic history of a monotypic bonebed composed by several individuals attributable to the dicynodont Dinodontosaurus sp. collected in a classic locality from the Dinodontosaurus Assemblage Zone (Middle Triassic of Brazil). Following the estimation of the minimal number of individuals, we analyzed several biostratinomic processes, such as transport and fragmentation. The assemblage is composed of at least six individuals, all of which are juveniles (although of different sizes), packed in close association and displaying different articulation levels, which indicates a moderate time of subaerial exposure before burial. The dispersion is comprised of bone elements of different Voorhies Groups, indicating the absence of hydraulic selection by transport and a short distance from the death site. The hypothesis of trampling is not discarded, as some bones show pre-burial cracks and fractures. The association of juveniles suggests that factors like insufficient nutrition, abandonment, and diseases could be the cause of death. The monotypic nature of the assemblage, when analyzed together with its possible taphonomic history, allows us to infer gregarious behaviour in Dinodontosaurus .